Growth Mindset in Early Childhood Teachers and the Transformation of Children’s Behavior - Theresia Alviani Sum (Qualitative Research in Early Childhood Education, 2026)
Early childhood education teachers play a central role in shaping children’s learning behavior, yet limited research has examined how teachers in under-resourced contexts develop and apply a growth mindset in everyday practice. This study aimed to explore how early childhood education teachers in Manggarai Regency perceive, develop, and implement growth mindset principles and how these practices influence children’s behavior in the classroom. The study used a qualitative descriptive design involving 29 purposively selected teachers. Data were collected through open-ended questionnaires, documentation, and in-depth interviews, and were analyzed using thematic analysis. The findings show that most teachers demonstrated strong motivation for continuous professional learning, resilience in responding to instructional challenges, and adaptive teaching practices despite structural limitations. The data also indicate that growth mindset-based teaching contributed to positive changes in children’s behavior, including greater independence, curiosity, confidence, and willingness to participate in learning activities. These findings suggest that growth mindset functions not only as a personal belief system but also as a pedagogical orientation that strengthens reflective teaching and supports more responsive classroom environments. The study highlights the importance of context-sensitive professional development programs that help early childhood teachers sustain adaptive and supportive teaching practices in low-resource settings.